Liderazgo docente en la perspectiva de universitarios - Lázaro Hernández, Héctor Miguel (2020)
This work has as objective, to exhibit the role professors leaderships’ plays in academic education of future professionals, and to know the different ways professors perform leadership over student community. This investigation was carried out in Universidad Juárez Autónoma de Tabasco's business division. The implemented survey was empirical and based on a purposeful or convenience sample of 107 students belonging to Marketing and public accounting degree. The results reveal that a democratic leadership prevails.